1984
DOI: 10.1038/hdy.1984.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of enzyme polymorphisms in herring (Clupea harengus L.)

Abstract: SUMMARYSingle pair matings were performed to confirm the genetic basis of electrophoretic variants of several enzyme systems in north-east Atlantic herring (Clupea harengus) collected in spawning condition from the North Irish Sea. Mendelian inheritance of codominant autosomal alleles was established for Aat-2, Idh-2, Ldh-2 and Pgi. Crosses among Fum-1, Idh-1 and Sod homozygotes produced only homozygous offspring.This study also permitted the investigation of linkage relationships between polymorphic loci. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Numerous breeding studies have indeed shown that electrophoretic variation can be under simple genetic control (e.g. King 1984, May et al 1979. When breeding experiments are not possible because of long generation times or because of difficulty with captive propagation, the genetic basis of the banding variants may be inferred by other criteria.…”
Section: Electrophoresis Resolves Single-locus Mendelian Variationmentioning
confidence: 99%
“…Numerous breeding studies have indeed shown that electrophoretic variation can be under simple genetic control (e.g. King 1984, May et al 1979. When breeding experiments are not possible because of long generation times or because of difficulty with captive propagation, the genetic basis of the banding variants may be inferred by other criteria.…”
Section: Electrophoresis Resolves Single-locus Mendelian Variationmentioning
confidence: 99%